Gestión de talento humano y su incidencia en el desempeño laboral de la dirección de movilidad, tránsito y transporte del GADM Riobamba periodo 2016 - Moya Romero, Fernanda Johana (2018)
The present titling work is the management of human talent and its impact on the work performance of the Mobility, Transit and Transportation Directorate of the GADM Riobamba period 2016, he defined objectives based on the needs that must be met with the development of the proposal. Within the state of the art, several sources of bibliographical consultation were reviewed, where it was possible to include definitions directly related to the proposed topic, in the research methodology the descriptive was applied to establish the essential points that generate results, supported by the inductive method to collect indispensable theoretical sources for the execution of the performance evaluation. In the results it was known that the regulation that regulates the administration of human talent is the internal control rules of the Comptroller General of the State, which defines the policies that must be applied in a fiscal period, establishing the responsible and actions, knowing that these should be developed by the Department of Human Talent of the GADM, in relation to the evaluation, two instruments were applied to establish the levels of fulfillment of the functions, in conclusion the Mobility, Transit and Transportation Directorate, each one of the workers and employees have a level of knowledge appropriate to the assigned position, interacting with the other colleagues in the department, which reflect the different skills they have, reflecting a good work environment between each person within that establishment to meet the with the objectives set. So it is recommended to apply customer service talks to improve user satisfaction.